Characterization of Dietzia cercidiphylli C-1 isolated from extra-heavy oil contaminated soil. Issue 32 (3rd April 2017) - Dai, Xiaoli; Yan, Guangxu; Guo, Shaohui
Abstract : Dietzia cercidiphylli C-1 isolated from extra-heavy oil contaminated soil can efficiently degrade extra-heavy oil. Abstract : Bioremediation of extra-heavy oil contaminated soil has become a hot research field. It is difficult for extra-heavy oil to be degraded by bacteria. In this study, strain C-1 was isolated from Venezuelan extra-heavy oil-contaminated soil. Morphological, physiological and phylogenetic analysis identified strain C-1 as Dietzia cercidiphylli . The strain could degrade 25.58 ± 0.48% of extra-heavy oil at an initial concentration of 100 mg L −1 in 14 days with the degradation rate constant of 0.021 per day. GC-MS analysis demonstrated that the strain could effectively degrade medium (C13–C17) and longer (C44) length chain n -alkanes. This is the first report that the Dietzia strain can degrade extra-heavy oil, especially C44 n -alkanes. Dietzia cercidiphylli C-1 could be applied in extra-heavy oil contaminated soil bioremediation in the future.